2009
DOI: 10.1007/s10157-009-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of nephrotic syndrome by intensive lipid-lowering therapy in a patient with lipoprotein glomerulopathy

Abstract: Lipoprotein glomerulopathy (LPG) is a rare hereditary disease characterized by the accumulation of much thrombi material consisting of lipoproteins at the glomerular capillary lumen. Most patients show nephrotic syndrome; nearly half progress to chronic renal failure. Intensive therapy with lipid-lowering agents reportedly engenders clinical remission with histological resolution. We report the case of a 14-year-old Japanese female patient who had been in a nephrotic condition with hematuria from 4 years old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…In the 1990s, probucol was reported to be effective for reducing proteinuria in a patient with early stage LPG who did not exhibit nephrotic syndrome [12]. Later, lipid-lowering therapies, including fibrates, were reported to improve both proteinuria and glomerular lesions in nephrotic LPG patients [4][5][6]13]. Ieiri et al [4] reported that combination therapy with fenofibrate, niceritrol, ethyl-icosapentate and probucol resulted in clinical remission with histologic resolution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the 1990s, probucol was reported to be effective for reducing proteinuria in a patient with early stage LPG who did not exhibit nephrotic syndrome [12]. Later, lipid-lowering therapies, including fibrates, were reported to improve both proteinuria and glomerular lesions in nephrotic LPG patients [4][5][6]13]. Ieiri et al [4] reported that combination therapy with fenofibrate, niceritrol, ethyl-icosapentate and probucol resulted in clinical remission with histologic resolution.…”
Section: Discussionmentioning
confidence: 95%
“…Kinomura et al [6] reported that intensive combination therapy by adding bezafibrate and ethylicosapentate to statin dramatically decreased proteinuria. Just recently, Matsunaga et al [13] described a patient who had improved nephrotic syndrome after switching from probucol to bezafibrate and atorvastatin, in combination with ACEi and angiotensin II receptor blocker. In contrast, statin monotherapy did not seem to reduce urinary protein excretion, even though a remission of dyslipidemia was achieved [3,11].…”
Section: Discussionmentioning
confidence: 97%
“…Although LPG is known to have a poor renal prognosis, case reports of successful treatment with lipid-lowering therapy have been increasing [17][18][19][20][21][22][23]. Interestingly, the course of the urinary protein level in our patient closely paralleled his TG and cholesterol levels ( Fig.…”
Section: Discussionmentioning
confidence: 65%
“…78,98 Given these findings, the prevention of hypertriglyceridemia may be important in LPG treatment, and the efficacy of lipid-lowering agents including fibrates, as shown clinically and by pathology studies, has been reported in several cases in Japan. 66,88,[100][101][102] Additionally, Hu et al 82 compared patient and renal survival rates over 3 years between fenofibrate-treated and control groups, and they confirmed the significant availability of fenofibrate for LPG treatment. In contrast, in apoE2 homozygote glomerulopathy, fibrates have been used in some cases, but the effect is unclear.…”
Section: Treatments and Prognosismentioning
confidence: 89%